Proceedings of the 12th Annual SIGCSE Conference on Innovation and Technology in Computer Science Education 2007
DOI: 10.1145/1268784.1268842
|View full text |Cite
|
Sign up to set email alerts
|

Enthusing and informing potential computer science students and their teachers

Abstract: School curricula contain little direct Computer Science (CS) content, and pupil surveys confirm that pupils have little idea what CS is. A range of initiatives have been introduced by universities to address this problem, and so attract more CS students. This paper presents the Computer Science Inside… project, one such initiative, the primary goals of which are to provide materials for use in secondary school classrooms, and to motivate and prepare the teachers to deliver them. The materials are principally w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 4 publications
(2 reference statements)
0
18
0
Order By: Relevance
“…There is a belief that computing entails little more than learning how to use computers (eg using a word processor or spreadsheet) [23]. Students and careers teachers often have an incomplete idea of what CS can involve [12]. Even among first year university students there is some surprise at the contents of the CS syllabus [19].…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a belief that computing entails little more than learning how to use computers (eg using a word processor or spreadsheet) [23]. Students and careers teachers often have an incomplete idea of what CS can involve [12]. Even among first year university students there is some surprise at the contents of the CS syllabus [19].…”
Section: Background and Related Workmentioning
confidence: 99%
“…A variety of university-driven initiatives such as Greenfoot [16], CS Inside [2,12] and our own, cs4fn [11], have sought to address the disconnectedness between the pervasive use of the products of computer science technology, particularly by young people, and their lack of knowledge about how they work. These and other 'excite programs' [13] also aim to enthuse students about CS more generally, and increase their awareness of the topic, but also in the hope of increasing enrolment onto further CS courses.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, however, it has been found that UK schools have steadily reduced the CS content of computing courses. This has been replaced instead with ICT training material [7]. As a result, the main focus of CS courses has shifted away from the teaching of practical computing concepts.…”
Section: Introductionmentioning
confidence: 99%